2020
DOI: 10.18060/24767
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Manifestations of COVID-19: A Systematic Review

Abstract: Background: Coronavirus Disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2), is currently a pandemic. Although pulmonary health has been the primary focus of studies during the early days of COVID-19, development of a comprehensive understanding of this emergent disease requires knowledge of all possible disease manifestations in affected patients.     Methods: This PRISMA-compliant review focuses on cutaneous manifestations reported in COVID-19 patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Multiple nails and mucocutaneous manifestations of Covid-19, including maculopapular eruptions, urticaria and the acral vasculopathy such as pseudo-chilblain/pernio-like (COVID toe) were considered as primary or evolving signs of the clinical course of the infection. 14 Singh et al 15 infection through skin wounds caused by personal protective equipment. 15 The cutaneous presentations of 507 patients with Covid-19 was reviewed by Zhao et al 16 The skin polymorphic lesions, urticaria, erythema and chilblain-like were prevalent and observed after mean of 9.92 days following the beginning of systemic symptoms.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple nails and mucocutaneous manifestations of Covid-19, including maculopapular eruptions, urticaria and the acral vasculopathy such as pseudo-chilblain/pernio-like (COVID toe) were considered as primary or evolving signs of the clinical course of the infection. 14 Singh et al 15 infection through skin wounds caused by personal protective equipment. 15 The cutaneous presentations of 507 patients with Covid-19 was reviewed by Zhao et al 16 The skin polymorphic lesions, urticaria, erythema and chilblain-like were prevalent and observed after mean of 9.92 days following the beginning of systemic symptoms.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…14 Singh et al 15 infection through skin wounds caused by personal protective equipment. 15 The cutaneous presentations of 507 patients with Covid-19 was reviewed by Zhao et al 16 The skin polymorphic lesions, urticaria, erythema and chilblain-like were prevalent and observed after mean of 9.92 days following the beginning of systemic symptoms.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 The cutaneous signs of COVID-19, unlike many other symptoms, have been reported in patients of different ages. 5 Even though early case studies rarely identified skin abnormalities, probably due to the inability to conduct a comprehensive cutaneous examination, subsequent research has revealed considerably greater rates of skin involvement. Several reports were published with descriptions of morbilliform, urticaria, erythema multiforme, Kawasaki, Grover's, vasculitis-like, livedo, retiform, and vasculopathy as well as others.…”
mentioning
confidence: 99%